UNVEILING THE VEIL: UNEARTHING STRUCTURAL VIOLENCE AGAINST WOMEN IN TEHSIL DAGGER DISTRICT BUNER - Liaqat Ali; Afzal Khan; Shahab Uddin (International Journal of Contemporary Issues in Social Sciences, 2024)
The research endeavor delves into the examination of structural violence perpetrated against women within Buner, with a specific focus on the Tehsil Dagger. Its overarching aim is to dissect the nuanced manifestations, root causes, and consequential ramifications of such systemic oppression upon the female populace in the region. The study concentrates predominantly on scrutinizing five key variables: the systematic deprivation of women’s educational access, the arbitrary negation of their entitlement to inherit property, the prevalence of coerced and underage marriages, the limited employment prospects for women, and their restricted involvement in political spheres within the locality. This scholarly pursuit holds considerable significance for stakeholders, policymakers, non-governmental organizations (NGOs), and governmental bodies alike, as it endeavors to illuminate the prevailing issue of violence targeting women. Methodologically, a blend of quantitative analysis and a case study approach has been adopted. Data collection involved a sample size comprising 382 respondents, drawn from all 17 Village Councils within the Tehsil. Ultimately, the researchers proffer recommendations and suggestions aimed at mitigating the identified challenges.